Engaging Students in Science: The Potential Role of “Narrative Thinking” and “Romantic Understanding” - Hadzigeorgiou, Yannis; Schulz, Roland M. (Frontiers in Education, 2019)
Engaging students in science and helping them develop an understanding of its ideas has been a consistent challenge for both science teachers and science researchers alike. Such a challenge is even greater in the context of the “Science for All” curriculum initiative. However, Bruner’s notion of “narrative thinking” and Egan’s “romantic understanding” offer an alternative approach to teaching and learning science, in a way that engagement and understanding become a possibility. This chapter focuses on students’ “narrative mode of thought”, as a bridge to understanding science—which has traditionally been based more upon the use of logico-mathematical thinking in the upper grades—and on a distinctive form of understanding the world, characteristic of students of the age range from eight to fifteen years. This latter form of understanding, that the educational theorist Kieran Egan calls “romantic understanding”, has features that can be readily associated with the natural world and its phenomena. Therefore its development could be fostered in the context of school science learning, and in a way that the narrative mode would also be taken into consideration.